2019
DOI: 10.26502/jesph.96120074
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Aspects of the High Blood Pressure in Occupational Environment-Case of a Bank in Cotonou (Benin)

Abstract: Introduction: Due to the heavy burden of morbidity, mortality, and inability to work, hypertension is a major challenge in the workplace. The purpose of this study was to identify the epidemiological characteristics of hypertension among bank employees in Cotonou.Methodology: This was a descriptive and transversal study of bank workers in Cotonou (Benin). The data were collected using the World Health Organization (WHO) STEPwise questionnaire adapted to our context, as well as blood pressure (BP), weight and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…The association between age and hypertension is common,22 39 with the risk of hypertension increasing with age. Several studies in the occupational sector have also reported this observation, and all sectors of activity are concerned: telecommunications in Senegal,40 textile plant,21 flour milling29 and banking in Benin 20…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…The association between age and hypertension is common,22 39 with the risk of hypertension increasing with age. Several studies in the occupational sector have also reported this observation, and all sectors of activity are concerned: telecommunications in Senegal,40 textile plant,21 flour milling29 and banking in Benin 20…”
Section: Discussionmentioning
confidence: 63%
“…In the textile spinning sector, one study showed an association between hypertension and occupational stress as measured by the Karasek model 21. Several other authors have found similar results, but in the tertiary sector, Kusuayi Mabele et al 34 in Congo in 2015 and Hinson et al 20 in a bank in Benin in 2016. It should be noted that the prevalence of occupational stress varies from one sector of activity to another25 35 and that the risk of hypertension could be correlated with it.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The prevalence of hypertension varies from one sector of activity to another. In the tertiary sector, the prevalence of hypertension was respectively: 41.9% among employees of the Office de Gestion du Fret Multimodal (Congo Kinshasa); 32.52% among workers of the Ministry of Health (Benin 2012); 25.3% among employees of a bank (Benin 2016) [7] [8] [9]. Hotel workers have easy access to tobacco, alcohol, and are also subject to stress at work due to job insecurity, night work, and also customer demands.…”
Section: Introductionmentioning
confidence: 99%